Evaluation of treatment outcomes and tolerability in older patients with rectal cancer treated with radiotherapy accompanied by the G-8 geriatric score: TROD13–003 multicenter study - Güzelöz, Zeliha; Görken, İlknur Bilkay; Aydın, Barbaros; Sert, Fatma; Yalman, Deniz; Parvizi, Murtaza; Avcı, Gülhan Güler; Altınok, Pelin; Halis, Hatice; Ergen, Şefika Arzu; Akgün, Züleyha; Özkan, Elif; et al. (My University, 2024)
Introduction: The choice of treatment for rectal cancer often differs in older and younger patients, with the rate of radiotherapy use lower among older adults. In our daily practice, when evaluating a frail older patient with rectal cancer, we usually choose to give less treatment. This may be due to concern that the patient will not be able to tolerate radiotherapy. The Geriatric 8 score (G8GS) is a guide to evaluating treatment tolerability as it relates to frailty in older adults with cancer. The aim of this study was to evaluate treatment outcomes and tolerability in older patients with rectal cancer treated with radiotherapy (RT) accompanied by G8GS. Materials and Methods: Patients aged 65 and older with stage I-III rectal adenocarcinoma who were treated with RT and had a G8 evaluation were included in this multicenter retrospective study. Prognostic factors related to G8GS were calculated using Chi-square and logistic regression tests and survival rates were calculated by the Kaplan–Meier test using the SPSS v24.0 software. All p-values ?0.05 were considered statistically significant. Results: A total of 699 patients from 16 national institutions were evaluated. The median age was 72 years (range 65–96), and the median follow-up was 43 (range 1- 190) months. Four hundred and fifty patients (64%) were categorized as frail with G8GS ?14 points. Frail patients had higher ages (p = 0.001) and more comorbidities (p = 0.001). Ability to receive concomitant and/or adjuvant chemotherapy rates were significantly higher in fit patients (p = 0.002 and p = 0.001, respectively). No significant difference was observed in terms of grade 3-4 early and late toxicity for both groups. Cancer-related death was higher (p = 0.003), and 5- and 8-year survival rates were significantly lower (p = 0.001), in the frail group. Age and being frail were significantly associated with survival.
Keywords: Capecitabine; Fluorouracil; Biological Marker; Adjuvant Chemotherapy; Adjuvant Therapy; Age Distribution; Aged; Article; Cancer Mortality; Cancer Patient; Cancer Prognosis; Cancer Radiotherapy; Cancer Staging; Cancer Survival; Chi Square Test; Clinical Outcome; Cohort Analysis; Comorbidity; Conformal Radiotherapy; Controlled Study; Evaluation Research; Female; Fitness; Follow Up; Frail Elderly; G 8 Geriatric Score; Geriatric Assessment; Human; Kaplan Meier Method; Local Recurrence Free Survival; Logistic Regression Analysis; Major Clinical Study; Male; Metastasis Free Survival; Multicenter Study (Topic); Overall Survival; Patient Coding; Patient Selection; Proctitis; Prognostic Assessment; Radiation Toxicity; Rectal Adenocarcinoma; Rectum Cancer; Retrospective Study; Statistical Significance; Survival Rate; Therapy; Treatment Outcome; Treatment Tolerability; Very Elderly; Volumetric Modulated Arc Therapy; Adult; Data Analysis Software; Drug Therapy; Frailty; Geriatric Assessment; Radiotherapy; Rectal Adenocarcinoma; Rectum Cancer; Special Situation For Pharmacovigilance; Therapy Effect